Mental Toughness and Adaptability in Game Matches Towards Resiliency of Sepaktakraw Athletes - Orlanes, Angelica Araja; Fernandez, Ashlirey Mercado; Panganiban, John Angelo Enciso; Panganiban, Teejay Dela Cueva (CV Rezki Media, 2024)
Background: This study investigates how mental toughness and adaptability in game matches contribute to the resiliency of Sepaktakraw athletes in the field of competitive challenges. Objectives: This study explored the impact of mental toughness and adaptability on the resilience of Sepaktakraw athletes facing competitive challenges. Methods: Conducted during the 2023-2024 academic year, the research involved 60 male athletes aged 18-22 from Batangas State University, each with 4-8 years of experience in the sport. Using a descriptive-correlational approach, the study assessed athletes’ perceptions of mental toughness and resilience through the 4C’s Psychological framework—Challenge, Commitment, Control, and Confidence. Results: Findings highlighted the role of mental toughness and adaptability in strengthening athletes’ resilience. Consequently, the study proposed tailored training activities focused on enhancing these traits in gameplay. Presented in tabular form, each activity includes specific objectives designed to help athletes develop coping mechanisms for setbacks, maintain focus, and improve mental toughness. Conclusion: By engaging in these targeted training exercises, teamwork, and community interactions, athletes are expected to build the resilience needed to overcome competitive challenges and achieve success in Sepaktakraw.